An Aqueous Rechargeable Zn//Co3O4 Battery with High Energy Density and Good Cycling Behavior. Issue 24 (27th April 2016) - Wang, Xiaowei; Wang, Faxing; Wang, Liying; Li, Minxia; Wang, Yanfang; Chen, Bingwei; Zhu, Yusong; Fu, Lijun; Zha, Liusheng; Zhang, Lixin; Wu, Yuping; Huang, Wei
Abstract : An aqueous rechargeable Zn//Co3 O4 battery is demonstrated with Zn@carbon fibers and Co3 O4 @Ni foam as the negative and positive electrodes, respectively, using an electrolyte of 1m KOH and 10 × 10 −3 m Zn(Ac)2 . It can operate at a cell voltage as high as 1.78 V with an energy density of 241 W h kg −1 and presents excellent cycling. The battery is also assembled into a flexible shape, which can be applied in flexible or wearable devices requiring high energy.